Isotope signatures of atmospheric mercury emitted from residential coal combustion. (1st February 2021) - Li, Xinyu; Li, Zhonggen; Chen, Ji; Zhang, Leiming; Yin, Runsheng; Sun, Guangyi; Meng, Bo; Cui, Zikang; Feng, Xinbin
Abstract: Residential coal combustion (RCC) is a major source of atmospheric mercury (Hg) in rural areas of China, but little is known about the isotope signatures of Hg from this source. In the present study, the isotope compositions of speciated Hg (Hg 0, Hg 2+, and Hg p ) in flue gas emitted from RCC were investigated in two important coal-producing areas (Xingren (XR) and Jinsha (JS)) of Guizhou Province, Southwest China. The total Hg concentration in discharged flue gas is in the range of 1.80–9.65 μg/m 3 at the two sites, and the emission ratio reaches 99.87%. Isotope signatures of total Hg in flue gas are similar to those of Hg in feed coal, with near-zero Δ 199 Hg and negative δ 202 Hg (−1.47‰ for XR and −3.00‰ for JS) in discharged flue gas. Such isotope signatures are very different from those of Hg emissions from modern coal-fired power plants with much higher δ 202 Hg signals. Negative shifts from Hg 0 to Hg 2+ in flue gas for δ 202 Hg (−0.94‰) and Δ 199 Hg (−0.51‰) were observed, suggesting that both mass-dependent fractionation and mass-independent fractionation occurred during RCC. The nuclear volume effect produced by chlorine oxidation of Hg 0 to Hg 2+ may play an important role in the observed mass-independent fractionation in Hg 2+ . Without any air pollution control devices, RCC potentially increases the atmospheric Hg levels and has a negative-shifting impact on the δ 202 Hg of atmospheric Hg. Graphical abstract: Image 1 Highlights: Isotope signature of total Hg is consistent between flue gas and feed coal Obvious MDF occurred among different Hg species in the flue gas Significant MIF is observed for Hg 2+ due to the oxidation of Hg 0 RCC is an important Hg source and potentially impacts atmospheric Hg isotope composition